1984
DOI: 10.1093/carcin/5.8.1091
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the bioactivation of nitrosamines to mutagens by various animal species including man

Abstract: Dimethylnitrosamine, dipropylnitrosamine, methylethylnitrosamine, nitrosopiperidine and nitrosopyrrolidine were assayed for mutagenicity in the Ames test in the presence of hepatic postmitochondrial preparations isolated from the mouse, rat, hamster, pig and man. Prior to each mutagenicity assay all activation systems were fully characterised with respect to monoamine oxidase, mixed-function amine oxidase and mixed-function oxidase activities. The hamster was the most efficient activator for all nitrosamines f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Rodent CYP2E1 is known to metabolize many substrates, such as organic solvents, nitrosamines and drugs [ 20 ]. The variable levels of CYP2E1 availability and thus potency comparing rat, hamster and man resulted in different experimental results in both in vivo and in vitro studies suggesting induced hamster S9 being slightly more potent than induced rat S9 to activate nitrosamines including small N-nitrosodialkylamines [ 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent CYP2E1 is known to metabolize many substrates, such as organic solvents, nitrosamines and drugs [ 20 ]. The variable levels of CYP2E1 availability and thus potency comparing rat, hamster and man resulted in different experimental results in both in vivo and in vitro studies suggesting induced hamster S9 being slightly more potent than induced rat S9 to activate nitrosamines including small N-nitrosodialkylamines [ 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, there exist several reports indicating that the activation of N-Nitrosamines by the liver microsomal fraction is species dependent [ 21 , 26 , 27 ]. In general, hamster S9 was shown to highly activate some N-Nitrosamines while rat S9 sometimes failed and, in particular, it was shown that N-nitrosodimethylamine (NDMA) and N-nitrosodiethylamine (NDEA) were mutagenic in TA1535 with hamster S9 but not with rat S9 [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phillipson and Ioannides (1984) put in evidence that some nitrosamines are activated to a different extent by liver S9 obtained from different mammals; the hamster was the most efficient activator followed by the mouse. Species differences were observed in the genotoxic effects of phenacetin and paracetamol in primary cultures of hepatocytes (Holme and Søderlund, 1986).…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…Distlerath and Guengerich, 1987 Buening et al, 1978;Bartsch et al, 1979;Dybing et al, 1979;Sabadie et al, 1980;Beaune et al, 1985;Mori et al, 1986;Neis et al, 1986;Raineri et al, 1986;Yamazaki et al, 1986;Jongeneelen et al, 1988;Smith andChipman, 1988 S9 S9 Ames et al, 1973;Tang and Friedman, 1977;Phillipson and Ioannides, 1983, 1984, 1989Le et al, 1985 S9 S9 S9 hazard identification Lijinsky and Andrews, 1983;Maron and Ames, 1983;Callander et al, 1995;Mortelmans andZeiger, 2000 Johnson 1996 Maron and Ames, 1983;Hakura et al, 1999Hakura et al, , 2003 S9 mix S9 10 0.5 mL S9 mix 0.05 mL S9 fraction, 1 mg protein/plate Cofactor I Ames 3 benzo a pyrene BP TA100 2-amino-3-methylimidazo 4,5-f quinoline IQ TA98 dimethylnitosamine DMN YG7108 Yamada et al, 1997 In Vitro Technologies S9 for 20 minutes with the same amount of S9 protein 1 mg/plate . The mutagenicity of BP, IQ, and DMN was assayed in the TA100, TA98, or YG7108 strain.…”
Section: S9mentioning
confidence: 99%